The relationship between Universiti Utara Malaysia library services and student satisfaction - Kamal Azmi, Mohd Syazwan; Othman, Mohd Zainudin (Universiti Utara Malaysia, 2020)
Customer satisfaction is important in ensuring the comfort of users in an organization. Students who are the customers of an educational institution have their own needs to be fulfilled by the institution’s management. The objective of this study is to find the extent of student satisfaction towards library services in UUM. The sample of the study was 200 students. The design of this study is a case-study survey using the quantitative approach. The survey form was used as an instrument for obtaining research data. The data obtained were analysed using percentage, frequency, mean score and standard deviation through Statistical Package for Social Science (SPSS) software. The findings also show that there are differences in the level of satisfaction of STML students by age, race and type of program in terms of facilities, except library facilities. Meanwhile, the findings for the service show that there are some differences in the level of satisfaction of STML students in all categories of services such as staff, environment and materials provided by UUM. The research’s results show that the level of student satisfaction towards library services at UUM is strong. The results of this study can be used as a guide to the management to improve the quality of the services and facilities provided to the students.